Febuxostat Attenuates Renal Damage besides Exerting Hypouricemic Effect in Streptozotocin-Induced Diabetic Rats - Jianmin Ran; Gang Xu; Huixuan Ma; Hailing Xu; Yan Liu; Rongshao Tan; Ping Zhu; Jun Song; Gancheng Lao (International Journal of Nephrology)
Aim. In this study, we aimed to investigate the effects of febuxostat, a novel inhibitor of xanthine oxidase (XO), on renal damage in streptozotocin- (STZ-) induced diabetic rats. Methods. Diabetes was induced by the intraperitoneal injection of STZ in male Sprague-Dawley rats. Sham-injected rats served as controls. The control and diabetic rats were treated with and without febuxostat for 8 weeks, respectively. Fasting blood and 24-h urine samples were collected every 4 weeks. Rat livers were extracted for detecting gene expression, content, and bioactivity of XO. Results. Diabetic rats showed significantly increased serum uric acid (SUA), serum creatinine (SCr), and urea nitrogen (BUN) levels. Daily urinary albumin (UAE), uric acid (UUA), and creatinine (UCr) excretion were also significantly increased in these rats. In diabetic rats, at week 8, febuxostat decreased SUA by 18.9%, while UAA was increased by 52.0%. However, UCr and urinary urea nitrogen (UUN) levels remained unchanged, while SCr and BUN levels decreased by >30% in these rats. Although hepatic gene expression, content, and activity of XO increased significantly in diabetic rats, febuxostat only slightly decreased its content. Conclusions. Febuxostat significantly attenuated renal damage in STZ-induced diabetic rats in addition to exerting hypouricemic effect.